Managing salts while irrigating with wastewater - Qadir, Manzoor; Drechsel, Pay (CAB International, 2010)
Where freshwater resources are scarce for reasons of climate or water pollution, urban waste-water is often used to irrigate a range of crops in support of urban markets as well as the livelihoods of farmers. As in many developing countries wastewater treatment is insufficient, the water can contain different types and levels of mostly undesirable constituents. In this review, the focus is on elevated salt concentrations from domestic or industrial origin, which can especially in long-term irrigation systems result in environmental and productivity constraints. As treatment options to reduce water salinity are resource-intensive, off- and on-farm management strategies are needed to offset the implications of saline wastewater. The sources of salts in wastewater can be reduced before it reaches the farm by (1) technologies in industrial sector that reduce salt consumption vis-à-vis discharge into the sewage system; (2) separation of high-salt releasing industries' wastewater from domestic and municipal wastewater; (3) reduced evaporation in wastewater treatment ponds; and (4) restrictions on using certain domestic products that are major sources of salts in wastewater. Besides the off-farm interventions, on-farm management strategies may address (1) selection of crops or crop varieties capable of producing profitable yield with saline wastewater; (2) selection of irrigation methods reducing salt levels or crop exposure to salts; (3) application of wastewater in excess of crop water requirement to leach excess salts from the root zone; (4) irrigation of wastewater in conjunction with freshwater through cyclic and/or blending interventions; (5) use of different agronomic interventions; (6) the application - where possible - of calcium-supplying amendments while irrigating with highly sodic wastewater to mitigate sodium effects on soils and crops; and (7) potential use of saline wastewater, if containing adequate proportion of calcium, to ameliorate sodic and saline-sodic soils. Since saline wastewater can also contain other contaminants than salts it is different from saline drainage or groundwater, and its long-term irrigation may result in the movement of, for example, nitrates, metal ions and metalloids to groundwater. Therefore, monitoring of groundwater quality in well-drained wastewater irrigation schemes is important, particularly where groundwater is used elsewhere for drinking purposes. In addition, crop and soil quality analyses are necessary to determine potential negative implications of wastewater irrigation on crop growth and food safety in general and for microbiological and/or other chemical constituents.